(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2008)
Introduction, modelling, issue to be addressed by ecosystem modelling, model types and attributes, best practice in escosystem modelling.
Keywords: Fishery management,Ecosystem management,Fishery policy,Quản lý nghề cá,Chính sách thủy sản,Quản lý hệ thống sinh thái